Effect of DFT Exchange Correlation Functionals and basis set Quality on the Calculations of the Magnetic Coupling Parameter J (Global Journal of Science Frontier Research, 2019)
The J magnetic coupling parameters were calculated theoretically by the aid of ORCA software. Seven exchange-correlation functionals combined with seven different basis set including low quality and high quality types. The calculations were done for two different geometries of the same dimer anion Cu2Cl6. The first geometry is a square planar, the second is distorted tetrahedral. The differences is due to the accompanied cation. For testing the approach the calculations have extended to the other dimers using only two combinations of the above that seems to give good results. The values of the computed J for all cases were compared to experiments. It termed out that some of the combinations functionals/basis set gave satisfactory results for both anion. A regression analysis were done to correlate the coupling constant with certain theoretical parameters chosen carefully for the above combinations. Because the electronic transitions are sensitive to small geometry variations of the same anion , we have used different approaches to calculate the first two transitions (mainly d-d).
Keywords: magnetic coupling parameter; DFT calculations; copper dimers